Adult acne a medical and psychological challenge of modern dermatology - Marzęda, Madalena; Blicharz, Agnieszka; Swatko, Tomasz; Małek, Anna (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Acne is a dermatological condition usually associated with adolescents. Although acne occurs less frequently in adults, it can have a major impact on self-esteem and functioning in daily life. In the adult population, acne is far more common in women than in men. Brief description of the state of knowledge: Adult acne lesions are usually localised in the U-zone, i.e. around the chin, jawline and mouth. There are several forms of adult acne, depending on the time of onset and clinical picture. Several factors are responsible for the occurrence of adult acne. The most important of these are the colonisation of the skin with the anaerobic bacterium Propionibacterium acnes, the overproduction of sebum and excessive keratinisation at the sebaceous gland mouths. In addition, chronic stress, nicotinism, sleep deprivation, obesity, as well as genetic predisposition, hormonal changes or sun exposure have a significant impact. The treatment of adult acne is difficult and long-lasting, usually combining pharmacology with cosmetological treatments. In the initial stage, it is based on topical retinoids, followed by the addition of azaleic acid, benzoyl peroxide and antibiotics. Summary: The treatment of adult acne is a challenge for dermatologists. It is important to inform the patient about the months-long course of the disease and treatment before the beginnig of treatment. Acne is often associated with lower self-esteem and reduced self-confidence, and even depression and relationship difficulties. For this reason, a holistic approach to the patient and treatment, is extremely important. With proper patient awareness, the chances of successful treatment are much higher.